Comparison of the Anxiety of Game and Combat Athletes of Catching Corona Virus - Feyzullah Koca (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The aim of this study is to compare the anxiety of catching the corona virus of game and combat athletes. Methods: A total of 351 university student athletes were asked to fill in the "Anxiety of catching the Corona virus" scale developed by Demir et al., (2020). Independent t-test and one-way Anova tests were used for statistical differences. Conclusion: The difference between the total scale scores of individual anxiety and anxiety of catching a new type of corona virus according to gender was statistically significant (p<0.05). The difference in social anxiety sub-dimension scores according to gender was not statistically significant (p>0.05). A statistically significant difference was found in the anxiety of catching coronavirus 19 according to the students’ game and combat sports (p<0.001). The anxiety of catching the corona virus is different for students who play games and fight sports. It has been determined that while the anxiety of catching corona virus 19 in university students who play games and combat sports varies according to gender and the type of sport they do, it is similar according to the sports age category. Students are moderately concerned about contracting coronavirus 19. The fact that the students who do combat sports have a higher level of anxiety than the students who play sports may be due to the close contact of the sports they are doing. In sports that require close contact, it can be recommended to use more mascots instead of paired exercises.